The benefits of the Legal Entity Identifier for monitoring systemic risk - François Laurent; Beata Kaminska; Carlos Aparicio; Bartosz Dworak; Luis Garcia; Dominique Durant; Lucia Ristori; Robert Kirchner; Romain Calleja; Eleni Katsigianni; Dimitrios Vitellas; Federico Pistelli (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper discusses the importance of the Legal Entity Identifier (LEI),1 particularly its role in monitoring systemic risk, and provides background material for Recommendation ESRB/2020/12 on identifying legal entities in order to support its implementation in the European Union.
Keywords: C81; E44; G28; 330; Legal entity identifier; Master data; Record Linkage; Trade register number; Systemic risk